A corona presidency in the coronavirus crisis? The dual task of the German presidency. Containing the crisis and giving a lasting impetus to European solidarity and autonomy - Eckhard Lübkemeier; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2020)
According to the dictionary, a 'corona' is the bright circle of light around the sun during a total eclipse. While the darkness of the corona pandemic is not total, the death toll and economic consequences that have come with it are devastating. This puts the EU 'to the greatest test' in its history, according to Chancellor Angela Merkel. Against this backdrop, Germany will take over the EU Council presidency on 1 July 2020 - caught between high expectations on the one hand, and the diminished influence of a presidency on the other. The task of the German presidency is twofold: Contain the negative fallout from the crisis and use its integrative momentum for the revitalisation of a crisis-prone European Union. Ultimately, EU members can only achieve this together, but the German presidency can contribute a great deal by forging compromises, providing incentives, and orienting itself towards the model of a solidarity-based and autonomous Europe - even beyond the Council presidency.
Keywords: 320